Preventive effect of mulberry (Morus alba) leaf tea on low-density lipoprotein and malondialdehyde levels in dyslipidemic sprague-dawley rats - Tia Rahmania Virdias; Mohammad Sulchan; Ahmad Ni’matullah Al-baarri (AcTion: Aceh Nutrition Journal, 2024)
A high-fat diet can lead to dyslipidemia, which is characterized by elevated levels of Low-Density Lipoprotein (LDL).  LDL is rapidly oxidized, resulting in oxidative stress. This increase in oxidative stress can lead to lipid peroxidation, ultimately producing Malondialdehyde (MDA). One way to prevent increased LDL and MDA levels is to consume mulberry leaf tea (MLT). This study aimed to analyze the effects of MLT administration on LDL and MDA levels in dyslipidemic Sprague-Dawley rats fed a high-fat diet (HFD). This study was conducted in 2021 at the Laboratory of the Center for Food and Nutrition Studies at Gadjah Mada University, Yogyakarta. True experimental research with a randomized pre- and post-test control-group design was used in this study. Thirty male Sprague-Dawley rats were used in this study. After 21 days of intervention, LDL and MDA levels were analyzed using CHOD-PAP and ELISA, respectively. One-way ANOVA and Kruskal-Wallis tests were used for statistical analyses. The administration of 36 mg and 72 mg of MLT for 21 days was able to have a significant effect on reducing LDL (p= 0,000) and MDA (p= 0,000) levels. In conclusion, mulberry leaf tea decreased the LDL and MDA levels in Sprague-Dawley rats fed a high-fat diet.